Clinical outcomes with the Kanso™ off-the-ear cochlear implant sound processor. - Mauger, Stefan J.; Jones, Marian; Nel, Esti; Del Dot, Janine (International Journal of Audiology, 2017)
Objective: To investigate clinical outcomes and subjective ratings of the Kanso™ off-the-ear (OTE) cochlear implant sound processor.Design:Prospective, within-subject design investigating outcomes with a range of single and dual-microphone programmes for Kanso compared to conventional behind-the-ear (BTE) sound processors.Study sample: Twenty post-lingually hearing-impaired cochlear implant recipients who were experienced Nucleus® 5 or Nucleus® 6 BTE users.Results: No significant difference in performance was found for words in quiet or sentences in co-located noise between the Kanso and Nucleus 6 devices. For the moderately directional Standard programme, no significant difference was found for sentences in spatially separated noise between the Kanso and Nucleus 6 devices, but a performance decrement between 1.4 and 2.0 dB was found in highly directional and adaptive directional programmes. The default Kanso programme, SCAN, provided improvements of 6.9 dB over a single-microphone programme and 2.3 dB over the Standard programme in spatially separated noise. Participants rated Kanso significantly better than their own BTE processor on measures of comfort, look and feel, ease of use, music and overall hearing performance.Conclusion: Dual-microphone directional processing provides significant benefit over a single microphone for OTE processors. This study demonstrates clinical outcomes and acceptance of the Kanso OTE sound processor.